Substantiation of costs model for operation of air navigation equipment - Яшанов, І. М. (Science-based technologies, 2020)
The article is devoted to the substantiation of costs model for the operation of electronic navigation equipment. The equipment of air navigation includes a set of ground, near-ground and onboard technical means, the quality and reliability of which largely influences on the safety and regularity of civil aviation. These include ground radio navigation and radar systems, radio communications, and automated air traffic control systems, which generate and provide consumers with information on flight parameters along the entire route from take-off to landing. The tasks of maintaining the required level of efficiency and reliable operation of these equipment are solved in the operation systems. The article considers the issues of obtaining analytical relations and determining mathematical relations for estimating the cost of resources for current repairs. Normative documents usually use such a concept of cost indicator as mathematical expectation, although the efficiency of resource costs for current repairs are objectively random variables and therefore the most complete characteristic is the probability density function or a number of characteristics, not only mathematical expectation but also variance, asymmetry, kurtosis and other moments of a higher order. In this paper, the author considered two options for financing repair procedures. The first option is related to the case when the level of the reserve for repairs is determined at the level of mathematical expectations. The second option is related to the case when the maintenance and repair system has a reserve of resources for repair procedures, which differs from the traditional approach to cost planning. The article analyzes the results of calculations of mathematical expectations of resource costs for different levels of interest rates and different indicators of reserve funds. Analytical relations are obtained to solve the problem of optimal choice of the resource fund for current repairs. At the same time, modeling was performed and histograms were constructed for different values ​​of reserve funds for repairs. Based on theoretical calculations, a nomogram is constructed, which shows that at certain interest rates there is an optimal value of total operating costs. The research results can be used in the process of designing and improving the operation systems of ground-based air navigation equipment.